THE HALF-YEAR MONITORING OF METEOROID INFLUX TO THE NEAR-EARTH SPACE BY TV-OBSERVATIONS - Kartashova, A. P.; Bagrov, A. V.; Bolgova, G. T.; Leonov, V. A. (Одеські астрономічні публікації, 2017)
The Astronomical Institute of Russian Academy of Science provides TV-meteor observations since 2000. We began them with hybrid camera for Space Control Survey, but now we use 6 simple wide-angle Patrol Camera (PatrolCa) for every-night monitoring of bright (up to 5m) meteors in zenith region nearly 2400 square degrees, and high-sensitive hybrid camera FAVOR with limiting magnitude for meteors about 9m...10m in field of view 400 square degrees. Our aim is correct estimation of meteoroid influx to the Near-Earth space. Results of half-year monitoring are presented in this paper, including distribution of meteors by time, by magnitude, by hour frequency etc. It is underlined, that earlier revealed depression of number of meteors with brightness 5m...6m due to the Poynting-Robertson drag is confirmed. The work was supported by RFBR grants 06-0208313 and 06-02-16365.